Evaluation of potential for water hyacinth leaf protein concentrate as a protein source in tilapia feeds : a case study in Pak-Phanang Southern Thailand - Ong Moc Quy; Yakupitiyage, Amararatne; Somsak Boromthanarat; Gallardo, Wenresti G.; Bhujel, Ram Chandra; Swedish International Development Agency (Sida) (Pathum Thani, Thailand : Asian Institute of Technology, 2008)
Leaf protein concentrate extracted from water hyacinth (WH -LPC) was regarded as potential plant protein to supplement in tilapia feed through tw o trials. In trial 1, WH-LPC was extracted by acid and heat coagulated method at acidifi cation at pH lower than 4.0, thermal precipitation at 50 0 C and rinsing with water. The WH-LPC obtained was evaluate d for conversion rate as well as gross composition. In trial 2, to determine alternative level of WH-LPC to soybean in formulated feed for tilapia cage culture. There were seven treatments that included commercial feed and six replacing level of WH-LPC 0%, 5%, 10%, 15%, 20% and 25% crude protein in formulated feed containing 3 0 % crude protein. Nile tilapias ( Oreochromis niloticus ) (average weight 8.0 g) were stocked at 30 fish per cage. The trials were designed by randomized complete block de sign. The result of trial 1 shown that LPC and protein yields obtaine d 0.047g dry matter and 0.017g crude protein 100 g -1 fresh water hyacinth biomass, respectively or 0.43 g dry matter and 0.15 g crude protein 100 g -1 fresh leaf water hyacinth respectively. In addition, proximate compositions of WH-LPC were analyzed at 35.99% crude prot ein, 1.49% crude lipid, 8.89% ash and 12.69 % crude fiber. The result of trial 2 presented that WH-LPC could completel y substitute soybean meal in tilapia formulated feed and replacing level of WH-LPC up to 15% crude protein that could give better growth performance, survival rate and efficienc y of protein of Nile tilapia. However, fish fed diets containing most of plant protein wer e less growth performance, efficiency of feed utilization and economic efficiency tha n fish fed commercial feed (P<0.05). In summary, using WH-LPC as protein sources in tilapia feed was remarked to be uneconomical efficiency, but it contributed a greatly role in i mproving environment, supplying protein sources and creating new jobs to improve livelihood for local people.
A thesis submitted in partial fulfillment of the requirem ents for the degree of Master of Science in Aquaculture and Aquatic Resourc es Management, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 2008
Keywords: Water hyacinth as feed; Tilapia -- Feeding and feeds